(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of the present study is to acquire an in-depth knowledge of the attitude of the consumers especially in the urban areas and the key factors involved in dealing with certain kinds of perishable foods. These days, the middle-class people showing greater interest in spending and shopping which has, of course, changed the shopping environment. This is the reason we could see a certain rise in the number of supermarkets in several developing countries like India. Moreover, there are several supermarkets which have been selling the perishable food items in India which was only available in the flea markets or as it is known in the local term “Kirana Bazar”. Due to the unavailability of suitable infrastructure, almost all kinds of agro-products reach the urban markets after a long haul. Moreover, there are several middlemen involved in the whole process which raises concerns about the quality and price of these perishable agro-products. Most of the time, the consumer behavior regarding these perishable products remain unknown and unidentified. Thus, the market has remained so-so for many decades and the problems the consumers face have remained unnoticed in the emerging economies like India. In this study, data is collected from one hundred consumers who market perishable products both from the flea markets and super markets in the city of Lucknow. The collected data is analyzed from several perspectives like the importance of the products, the expectations of the consumers, and the perceived and actual levels of values of the perishable food products to find the gap between what people get actually and what they expect.